Bio-efficacy of mosquito mat vaporizers and associated detoxification mechanisms in Aedes mosquitoes; and community perception on the use of household insecticide products / Azratul Hizayu Taib - Azratul Hizayu , Taib (2022)
Since the early 1980s, electric vaporizing mats, which combine a mat heater and a vaporizing mat, have grown in popularity. This notable method has the advantage over coils in producing no visible smoke. Burning mosquito coils, heated mats or vaporizers are slow-release household insecticides that are most likely to cause long-term low-level exposure. A statewide investigation was carried out to (1) evaluate the bio-efficacy status of Aedes aegypti and Aedes albopictus populations against mat vaporizers in Selangor, (2) characterize detoxification mechanisms of pyrethroid resistance in Ae. aegypti and Ae. albopictus in Selangor, (3) access the knowledge, attitudes and practices regarding household insecticides use in residential areas in Selangor. Mosquito mat bioassays indicated that Ae. albopictus was more susceptible than Ae. aegypti in the studied populations. Aedes aegypti was resistant to prallethrin > prallethrin with piperonyl butoxide (PBO) > dimefluthrin > d-allethrin. Meanwhile Ae. albopictus was resistant to dimefluthrin > prallethrin > prallethrin with PBO > d-allethrin. In enzyme microassays, elevated levels of α-esterases, β-esterases, mixed function oxidases and glutathione-S-transferase activities were demonstrated in majority of the populations of Ae. aegypti and Ae. albopictus. Besides, correlations between prallethrin with PBO with glutathione-S-transferase activity, and prallethrin with glutathione-S-transferase activity were also demonstrated in Ae. aegypti. An association between activity of α-esterases and β-esterases was also demonstrated in Ae. aegypti. For Ae. albopictus, associations between activity of α-esterase with β-esterases, α-esterases with mixed function oxidases and β- esterases with mixed function oxidases were demonstrated. Knowledge on mosquito in Selangor community was associated with age, gender, ethnicity and household income. However, no factors were associated with attitudes on household insecticide use. Factors associated with practices on household insecticide use were age and attitudes. The findings of this study demonstrated that Ae. albopictus was more susceptible than Ae. aegypti with d-allethrin as the most the effective active ingredient for both species. This data may also assist local authorities in providing susceptibility baseline and appropriate dosage of active ingredient to be used in household insecticide products. Further, application of biochemical tool could also provide significant insights into the evolution and adaptation of Malaysian Aedes mosquitoes as a consequence of frequent insecticide exposure. The present study also offers an opportunity to understand the users’ behaviour on the use of household insecticide products, and consequently allows the implementation of strategic measures for Aedes control programs in Malaysia.